HYPERCALCEMIC HYPERPARATHYROIDISM WITH UNIDENTIFIABLE PARATHYROID ADENOMA: THE LIMITATIONS OF IMAGING MODALITIES - Joshi, Nidhi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Symptomatic hyperparathyroidism is often missed. After confirming autonomous hyperparathyroidism, identifi- cation of a single culprit gland is impeded by limitations in imaging modalities. Although the culprit gland has been identified as the adenoma, recurrence in the remaining glands is also worrisome. CASE We present a case of a female diagnosed with autoimmune hypothyroidism with proximal muscle weakness who self-medicated with NSAIDs and homeopathic tablets. Laboratory examinations revealed persistently elevated serum calcium with low phosphorus despite discontinuation of the above medications. Normalization of TSH with thyroxine has been achieved within 6 weeks. Hypercalcemia was attributed to autonomous hyperparathyroidism. Initial imaging did not reveal any nodule in the neck nor an uptake in nuclear imaging. Originally, a parathyroidectomy with autotransplantation of half a normal parathyroid into the sternocleidomastoid muscle was planned, however, the patient refused any surgical intervention. Instead, she was started on medical therapy with cinacalcet. Following a year of therapy, due to the cost of cinacalcet in India, the family opted for surgery. A pre-operative computed tomography scan of the neck revealed a nodule in the right paratracheal region. Total parathyroidectomy with autotransplantation of half of the normal gland was done. CONCLUSION In India, fortifying food with vitamin D is not done. Nutritional deficiencies may contribute to the development of secondary hyperparathyroidism and tertiary hyper- parathyroidism if untreated. In the management of these conditions, the role of total parathyroidectomy and autotransplantation cannot be discounted.